2014
DOI: 10.1161/hypertensionaha.113.02550
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association of Olmesartan and Other Angiotensin Receptor Blockers With Overall and Cause-Specific Mortality

Abstract: Because these drugs are now widely used in large populations, it would seem appropriate to undertake a large-scale analysis to compare the mortality risks associated with each agent in patients with different clinical indications. WithinAbstract-Concerns about an increased cardiovascular risk with the angiotensin receptor blocker, olmesartan, prompted the current study to examine associations between olmesartan and other angiotensin receptor blockers with overall and causespecific mortalities. We collected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Moreover, the study population taking ARBs was relatively small ( n = 3490). A study in Taiwan that analyzed a large number of patients ( n = 690,463) from claims data compared the effects of six ARBs (candesartan, irbesartan, losartan, olmesartan, telmisartan, and valsartan) and found that olmesartan did not increase long‐term cardiovascular risk compared with that by losartan 28 . This study deserves attention in that it elucidates the effect of olmesartan, unlike previous studies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the study population taking ARBs was relatively small ( n = 3490). A study in Taiwan that analyzed a large number of patients ( n = 690,463) from claims data compared the effects of six ARBs (candesartan, irbesartan, losartan, olmesartan, telmisartan, and valsartan) and found that olmesartan did not increase long‐term cardiovascular risk compared with that by losartan 28 . This study deserves attention in that it elucidates the effect of olmesartan, unlike previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…A study in Taiwan that analyzed a large number of patients ( n = 690,463) from claims data compared the effects of six ARBs (candesartan, irbesartan, losartan, olmesartan, telmisartan, and valsartan) and found that olmesartan did not increase long‐term cardiovascular risk compared with that by losartan. 28 This study deserves attention in that it elucidates the effect of olmesartan, unlike previous studies. However, the study population was more heterogeneous as patients with underlying CVD were not excluded, contrary to the case in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 In addition, there are concerns that olmesartan may increase cardiovascular risk. 29 To compare the new drug azilsartan to reference treatments, White et al 24 conducted an NI trial with two new treatments (azilsartan 40 mg and azilsartan 80 mg), two reference treatments (olmesartan 40 mg and valsartan 320 mg) and a placebo. The primary efficacy endpoint is the change from baseline in 24-h mean systolic blood pressure (BP).…”
Section: Examplementioning
confidence: 99%
“…18 Previous studies already have suggested that compared with other ARBs, olmesartan shows higher blood pressure-lowering effect, therefore, probably could contribute in reducing CVD risk. In addition, various meta-analyses have supported that olmesartan is not correlated with increased cardiovascular risk 19,20 and is currently used widely as antihypertensive medication.…”
mentioning
confidence: 99%